2005
DOI: 10.3354/meps292013
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity of bacterioplankton assemblages in western Antarctic seawaters during late spring

Abstract: Functional diversity and aminopeptidase activity (AMA) in bacterial assemblages were determined in western Antarctic waters during late spring 2002. Functional diversity was assayed by the patterns of sole carbon source utilization in Biolog-ECO Microplates TM and AMA with the fluorogenic substrate leucine 7-amido-4-methylcoumarin. N-acetyl-D-glucosamine and D-cellobiose were the most used carbohydrates. This suggested that used dissolved organic carbon (DOC) was mostly of either zoo-or phytoplankton origin. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(18 citation statements)
references
References 43 publications
(48 reference statements)
0
11
1
Order By: Relevance
“…The LAP/GLU ratio in our study was different from the ranges observed by Sala et al [14] in the Arctic ocean (85-100), and from temperate regions (as in the oligotrophic Mediterranean Sea) where LAP prevail over other enzymatic activities [13,46]. Nevertheless, a prevalence of GLU on LAP was observed in Arctic fjords [20], and this suggests that patterns of peptide hydrolysis may differ between temperate and high latitude sites [52]. A higher hydrolysis potential for polysaccharides relative to proteins in Arctic Ocean, was showed [45], reflecting changes in OM structure between the water masses.…”
Section: Peculiar Eaa Expression Related To Pom Compositioncontrasting
confidence: 94%
See 1 more Smart Citation
“…The LAP/GLU ratio in our study was different from the ranges observed by Sala et al [14] in the Arctic ocean (85-100), and from temperate regions (as in the oligotrophic Mediterranean Sea) where LAP prevail over other enzymatic activities [13,46]. Nevertheless, a prevalence of GLU on LAP was observed in Arctic fjords [20], and this suggests that patterns of peptide hydrolysis may differ between temperate and high latitude sites [52]. A higher hydrolysis potential for polysaccharides relative to proteins in Arctic Ocean, was showed [45], reflecting changes in OM structure between the water masses.…”
Section: Peculiar Eaa Expression Related To Pom Compositioncontrasting
confidence: 94%
“…Carbohydrates can be relevant for microbial metabolism in the ocean since they are major constituents of phytoplankton and of marine particles from marine snow to large aggregates [16]; moreover, the GLU completes the hydrolysis of cellulose in marine particles [51]. In Arctic Surface Waters [14] and in western Antarctica [52], other Authors showed that bacterioplankton used preferentially carbohydrates, and the glycosidase assayed (i.e., beta-glucosidase, xylosidase, arabinosidase, and cellobiosidase) had high specific activities. In those studies, the influence of polar ice-melting was indicated as a leading factor.…”
Section: Peculiar Eaa Expression Related To Pom Compositionmentioning
confidence: 99%
“…The color development for each plate was expressed as averaged substrate color development (ASCD); i.e., ASCD = Σ ((R-C)/31), where R is the absorbance value averaged from three wells with substrate and C is absorbance value averaged from the control wells (without substrate) [41]. The substrate richness (catabolic richness, S) values, (i.e., total number of oxidized C substrates = total number of wells with absorbance over 0.10 OD) and the catabolic diversity index (Shannon functional diversity index, H) were computed together with the Shannon Evenness (E) index (H) calculated by the free software Past 3.14 for environmental data.…”
Section: Methodsmentioning
confidence: 99%
“…These techniques are dominated by methods to visualize microbial cells and to detect cellular biomolecules including nucleic acids and lipids (Kaštovská and others, 2007; Mikucki and others, 2009; Barnett and others, 2012a; Zarsky and others, 2013; Stibal and others, 2015). The microbial activity of glacial ice has been studied (1) by measuring the uptake of labelled substrates such as acetate and amino acids (Foght and others, 2004; Sala and others, 2005; Hodson and others, 2007), (2) through inferences from imbalances in carbon and sulphur ions (Sharp and others, 1999; Wadham and others, 2004) and (3) by quantifying methane production (Stibal and others, 2012). Together, these techniques can be used to provide insights into the presence, abundance, diversity or activity of microorganisms.…”
Section: Introductionmentioning
confidence: 99%